UNLOCKING IMPULSIVE PURCHASING: THE INFLUENCE OF FREE SHIPPING TAGLINES AND ONLINE CUSTOMER REVIEWS ON SHOPEE SHOPPERS - Azis Muthalib, Dzulfikri (Qawwam : The Leader's Writing, 2025)
This study aims to examine the influence of the "free shipping" tagline and online customer reviews on impulsive purchasing in Shopee e-commerce. The population of this study consists of students from the Management Department, Faculty of Economics and Islamic Business at Universitas Muhammadiyah Kendari, who have shopped on Shopee, with an unknown sample size. The sample for this study consists of 96 respondents. The data collection method used in this study is through questionnaires. This study employs multiple linear regression analysis. The results indicate that: the "free shipping" tagline and online customer reviews have a positive and significant influence on impulsive purchasing in Shopee e-commerce; the "free shipping" tagline has a positive and significant impact on impulsive purchasing in Shopee e-commerce; and online customer reviews have a positive and significant impact on impulsive purchasing in Shopee e-commerce. Keywords: Free Shipping Tagline; Online Customer Review; Impulsive Purchasing